(3SHd GdgOi hGdQTGO aj SjQI NjQ GdYHGO hPcQ aVGFdg hCYdGe fHhJg hCaYGdg hCMhGdg aj GdeHOC hGdeYGOs - (3GdTeS GdTGej , eMeO Hf jhSa Hf Ydj Hf jhSa, TeS GdOjf,J (B942 (3g` s
(3ChdgG (B:s
(3ai UaI UdGJg Udi Gddg Ydjg hSde hajg aQhY (B: (3GdChd ai JcHjQg Udi Gddg Ydjg hSde jOjg hVYgG Ydi GdUOQ s
(3BNQgG (B:s
(3Qhi ai ZRhI PGJ GdQbGY bUI CNQi eKd gPg aZf cGf GdhGbOi bO MaX eG PcQ ai gPg GdZRhI acCfgG bUJGf hGdgd CYde HGdUhGH Je GdedLO GdQGHY ef GdSjQI GdfHhjI s
(3HgG fXGe GdJYbjHIs
(3HOGNdgG HjGV hWjGQGJs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B155 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B12 - (3U (B131s
(3HQhcdeGf (B- (3GdLRA (B2 - (3U (B392 ; (3HQhcdeGf edMb (B- (3GdLRA (B2 - (3U (B415 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B2 - (3bSe (B5 - (3U (B129 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJGQjNs